Elevated Monocyte to High-Density Lipoprotein Cholesterol Ratio and Endothelial Dysfunction in Behcet Disease - AÇIKGÖZ, NUSRET; Acikgoz, NUSRET; Kurtoglu, Ertugrul; Yagmur, Julide; KAPICIOĞLU, YELDA; CANSEL, MEHMET; ERMİŞ, NECİP (My University, 2018)
Behcet disease (BD) is a multisystemic disorder characterized by endothelial dysfunction and inflammation. Monocyte to high-density lipoprotein cholesterol ratio (MHR) is a recently emerged indicator of inflammation and oxidative stress. Sixty patients with BD and 50 control individuals were included to investigate the relationship between MHR and endothelial dysfunction. Endothelial function was assessed by flow- and nitroglycerin-mediated dilatation technique (FMD and NMD, respectively). Serum high-sensitivity C-reactive protein (hsCRP) levels were measured in all study participants. The MHR and hsCRP levels were significantly higher in patients with active BD than in controls. Brachial artery FMD was significantly lower in patients with active BD than in controls. Brachial artery NMD was similar between groups. There was a strong inverse correlation between MHR and FMD and a strong positive correlation between MHR and serum hsCRP levels. Thus, elevated MHR may be a useful marker reflecting impaired endothelial function and systemic inflammation in patients with BD.